1998
DOI: 10.1295/polymj.30.414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Aging on Polarization-Induced Photodimerization in the Glassy Region of Poly(methyl methacrylate)

Abstract: ABSTRACT:Intramolecular photodimerization of the photochromic molecule 9-hydroxymethyl-10-[(l-naphthyl methoxy)-methyl]anthracene (HNMA) was investigated by ultraviolet-visible (UV-VIS) spectroscopy in the glassy region ofpoly(methyl methacrylate) (PMMA) under different aging conditions. The PMMA matrix was annealed for different time intervals in the glassy region after quenching from 140°C (37.8°C above the glass transition temperature (T 8 )). By following the photodimerization upon irradiation with linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…There seems to be no reason to take into account the expansion of the free volume, which could indicate that the increase in the free volume leads to an increase in the fractions of [cis] r /([cis] u + [cis] r ) and [trans] r /([trans] u + [trans] r ) by roughly the same factor. Previous measurements indicate that the activation energy E a of azobenzene is relatively independent of the exact structure of the azobenzene moiety, often yielding values around 20 kcal, ,,, which is completely in agreement with our experimental data.…”
Section: Discussionsupporting
confidence: 92%
“…There seems to be no reason to take into account the expansion of the free volume, which could indicate that the increase in the free volume leads to an increase in the fractions of [cis] r /([cis] u + [cis] r ) and [trans] r /([trans] u + [trans] r ) by roughly the same factor. Previous measurements indicate that the activation energy E a of azobenzene is relatively independent of the exact structure of the azobenzene moiety, often yielding values around 20 kcal, ,,, which is completely in agreement with our experimental data.…”
Section: Discussionsupporting
confidence: 92%
“…Prior to the experiments, all the samples were dried at 170°C in vacuo over 48 h to remove residual solvent. Since it has been found that the physical aging process of the polymer matrix affects the optical anisotropy induced by linearly polarized light, 10,11 all the samples were prepared with the same thermal history prior to the experiments.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…These characteristics lead push-pull azo dyes to the prospect of the new optical functional materials utilizing the second-order nonlinear optical effect [2][3][4] or photoinduced anisotropy. [5][6][7][8] A polarized light-induced anisotropy has been observed in polymer films including photochromic molecules. Since the 1980s, this type of anisotropy has been studied in polymers doped with azo dyes for transient polarization holography by Todorov and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…The push−pull type of azo dyes has important characteristics, i.e., the larger polarity than that of azobenzene without substituent, and the fast thermal reisomerization from cis to trans forms, because of a large charge separation induced by D and A. These characteristics lead push−pull azo dyes to the prospect of the new optical functional materials utilizing the second-order nonlinear optical effect or photoinduced anisotropy. …”
Section: Introductionmentioning
confidence: 99%